Optical band gap and electrical conductivity of doped conducting polypyrrole - Lanuza, Chiara Rosario Julia (Animo Repository, 2019)
Conducting polypyrrole thin films, doped with sodium-p-toluenesulfonate (Na-pTS) and potassium-hydroquinone monosulfate (K-HQS), were prepared by electrochemical oxidation of pyrrole on indium-tin-oxide/glass substrates. The optical band gaps of the doped polymer materials were determined from their UV-Vis absorption spectra. For polypyrrole doped with Na-pTS, increasing the doping level, from 0.10 M to 0.12 M Na-pTs decreases the optical band gap from 2.05 eV to 1.98 eV. Also, doping polypyrrole with K-HQS was found to produce lower optical band gap, i.e. 1.86 eV for 0.10 M K-HQS dopant molarity. The electrical conductivity of the Na-pTS-doped polypyrrole films, measured using van der Pauw technique, were found to increase with higher doping level; conductivity values range from 105 to 151 Ω-1cm-1. © 2019 IEEE.